Laser assisted flow deposition: a new method to grow ZnO - Rodrigues, J. (2013)
Zinc oxide (ZnO) has been one of the most studied materials in the last decades. Either as bulk material, epilayers or nanostructures, this direct wide band gap semiconductor is known to possess great potential for fundamental science and modern technology applications.